PEMBERDAYAAN SANTRI DAN MASYARAKAT MELALUI KEGIATAN EKONOMI KREATIF DAUR ULANG SAMPAH DI PONDOK PESANTREN AN-NASYIIN DESA GRUJUGAN KECAMTAN LARANGAN - Siti Qamariyah; Isbat Abdullah (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2022)
Islamic boarding schools, one of the traditional educational institutions that still exist, are the most subjective learning places in developing the character of students. In addition, the innovation and creativity of students can be collaborated with their imaginations with each other so that they can become a multi-talent hub that can be used as an inspiration for the community, including in the economic development of local communities. The purpose of this study is to empower students and the community through creative economic activities in recycling waste at An-Nasyiin Islamic Boarding School, Grujugan Village, Larangan District, Pamekasan. The research method is a qualitative research conducted by interview, observation and documentation. The results of this study are the process of empowering this waste recycling goes well according to what has been planned and also this activity gets a positive response from the surrounding community and also benefits from this creative economic activity. can already be felt by the community, students and Islamic boarding schools.